Syntactic Complexity of Online Opinion Articles Published in South East Asian Countries - Dwi Indarti; Muarif Muarif (Bina Nusantara University, 2022)
The research investigated the syntactic complexity of opinion articles published in online newspapers from English as a Second Language (ESL) and English as a Foreign Language (EFL) countries in South-East Asia (SEA). The aims of the research were, first, to analyze the types of Syntactic Complexity (SC) of opinion articles in online news media. The second was to seek the difference in syntactic complexity in online opinion articles between ESL and EFL countries. The third was to seek whether there was a significant difference in terms of types of syntactic measurements between ESL and EFL countries. To answer the questions, the research applied both quantitative and qualitative methods. Twelve opinion articles from online news media in SEA countries were derived from Malaysia and Singapore, which represented ESL countries, and Indonesia and Thailand, which represented EFL countries. The data were analyzed by using an L2 syntactic complexity analyzer. The Second Language Syntactic Complexity Analyzer (L2SCA) program displayed fourteen syntactic complexity measures divided into five types of measurements such as the length of production, sentence complexity, subordination, coordination, and particular structures. From comparing overall ESL and EFL countries and each of the opinion articles topics, the research results reveal that opinion articles of ESL countries show a higher score on the lengthof production, sentence complexity, subordination, and particular structures than EFL countries. Meanwhile, in coordination type, EFL countries display a higher number of a score than ESL ones. The research indicates there is no significant difference between ESL and EFL countries since the p-value of each type of syntactic complexity is higher than 0,05.